SHAPE-INDEPENDENT EXPANSION FOR THE (3)S(1)-(3)D(1) MIXING PARAMETER - Adhikari, S. K.; Tomio, L.; Demelo, JPBC; Frederico, T. (Elsevier B.V., 1993)
A low-energy shape-independent expansion is suggested for the function tan(2epsilon(BB))/(2k2), where epsilon(BB) is the Blatt-Biedenharn mixing parameter for the S-3(1)-3D1 channel. This expansion allows an evaluation of the mixing parameter epsilon(BB) from a knowledge of the deuteron asymptotic D to S ratio, pion mass and other low-energy observables, such as the scattering lengths, deuteron binding etc., of the nucleon-nucleon system. We demonstrate that the correct long range behavior of the tensor potential is essential for a realistic reproduction of epsilon(BB).